Não unicidade para uma classe de operadores do tipo parabólico - Rosas, Marco Antonio Moya (2022)
In this thesis we consider the non-uniqueness for a class of parabolic operators. We will prove that for certain real analytic perturbation of the Heat Operator there is a non unique solution for the Initial Value Problem.